The caribbean low-level jet, the inter-tropical convergence zona and the precipitation patterns in the intra-americas sea: a proposed dynamical mechanism - Hidalgo, H.G., Durán-Quesada, A.M., Amador, J.A. and Alfaro, E.J. (My University, 2015)
Data from the Global Precipitation Climatology Project covering Central America, the Caribbean Sea, the eastern tropical Pacific and northern South America are used to compute four indexes that describe characteristics of the Inter‐Tropical Convergence Zone: the latitudinal center of mass of precipitation, the longitudinal center of mass of precipitation, the average precipitation in a region bounded by 10° S-25° N and 100° W-55° W, and the spread of the precipitation patterns. A very strong correlation is found between summer latitudinal center of mass and a summer index of the Caribbean Low‐Level Jet suggesting connections between Pacific and Caribbean climatic processes. The sign of the correlation implies that when the jet is stronger (weaker) there is a lower (higher) latitudinal center of mass and at the same time less (more) precipitation in the Pacific slope of Central America. The connection between the Caribbean and Pacific climate is not only related to high‐level wind convergence, but it is proposed here that local convection and the establishment of a zonal circulation may be playing a role in the process. The circulation seems to be consistent during years when latitudinal center of mass is lower than normal, apparently reinforcing the jet, and presents weaker strength during years of high latitudinal center of mass. The proposed mechanism is explained in some detail.
Keywords: Caribbean Low‐Level Jet, precipitation, moisture, transport, Central America climatology, Atlantic Ocean, Pacific Ocean, Western Hemisphere Warm Pool